Система уравнений. двойная замена переменных   { x^2+y^2+2(x+y)=23 { x^2+y^2+xy=19

Система уравнений. двойная замена переменных   { x^2+y^2+2(x+y)=23 { x^2+y^2+xy=19
Гость
Ответ(ы) на вопрос:
Гость
(x+y)^2-xy=19 (x+y)^2-2xy+2(x+y)=23   -xy+2(x+y)=4 -xy=4-2(x+y)   x+y=t   t^2+4-2t=19 t^2-2t-15=0 t=5 t=-3   xy=t^2-19  xy=6                          xy=-10   x+y=5             x+y=-3 xy=6                xy=-10   (2;3)                (-5;2)  (3;2)                 (2;-5)
Гость
(x+y)^2-xy=19 (x+y)^2-2xy+2(x+y)=23 -xy+2(x+y)=4 -xy=4-2(x+y)  x+y=t t^2+4-2t=19 t^2-2t-15=0 t=5 t=-3   xy=t^2-19  xy=6  xy=-10 x+y=5  x+y=-3 xy=6 xy=-10 (2;3)  (-5;2)  (3;2) (2;-5)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы